Use of an Insulation-Tipped Knife during Rigid Bronchoscopic Treatment of Benign Tracheobronchial Stenosis - Ji-Won Park; Yousang Ko; Changhwan Kim (Medicina, 2021)
Background and Objectives: Tracheal or bronchial tears are potential complications of rigid bronchoscopy. This study aimed to investigate the acute complications and outcomes of using an insulation-tipped (IT) knife in combination with rigid bronchoscopic dilatation for treating benign tracheobronchial stenosis. Materials and Methods: We conducted a chart review of patients with benign tracheobronchial stenosis who were treated with rigid bronchoscopy and an IT knife at two referral centers. Treatment success was defined as a clinically stable state without worsening symptoms after 3 months of treatment. Results: Of the 23 patients with benign tracheobronchial stenosis, 15 had tracheal stenosis and 6 had main bronchial stenosis. Among them, three cases were of simple stenosis (13%), while the others were of complex stenosis (87%). The overall treatment success rate was 87.0%. Pneumomediastinum and subcutaneous emphysema occurred due to bronchial laceration in two cases of distal left main bronchial stenosis (8.7%), and no other significant acute complications developed. Silicone stents were inserted in 20 patients, and successful stent removal was possible in 11 patients (55.0%). Six of the seven stents inserted in patients with post-intubation tracheal stenosis were removed successfully (85.7%). However, most of the patients with post-tracheostomy tracheal stenosis required persistent stenting (80%). Pulmonary function was significantly increased after treatment, and the mean increase in the forced expiratory volume in 1 s was 391 ± 171 mL (160–700 mL). Conclusion: The use of an IT knife can be suggested as an effective and safe modality for rigid bronchoscopic treatment of benign tracheobronchial stenosis.